Ultrashort pulse fiber laser incorporating nickel-based metal-organic framework saturable absorber - Murad, Amir (2022)
Ultrashort pulse fiber lasers have drawn considerable research interest owing to their capabilities in providing research solutions for numerous advanced academic and industrial applications. The passive mode-locking method, using real saturable absorbers (SAs), has the prospect of constructing a simple, compact, robust and stable ultrashort pulse source. Until now, various materials have been successfully demonstrated for the fabrication of ultrashort pulse fiber lasers. However, the properties of these materials strictly depend on their intrinsic properties which require fine control and a deeper understanding of material properties. Therefore, this work demonstrates the fabrication of metal-organic framework (MOF)-based SA for ultrashort pulse generation. MOFs have developed an important class of crystalline, porous and hybrid materials with vast possible combinations, synergistic effects and tunable characteristics. This work involves the fabrication of SA using nickle-1,3,5 benzene tricarboxylic acid (Ni-H3BTC) MOF by varying metal to ligand ratio. Five different concentration samples were synthesized by increasing the metal ratio from 0.5 to 4.0 with respect to the fixed ligand ratio of 1.0. The prepared samples were characterized for structural, optical, electrical, dielectric and nonlinear saturable absorption properties. The properties of the prepared samples varied proportionally with increasing metal-to-ligand ratio. The prepared samples were further explored for ultrashort pulse generation. The composite of prepared materials and polydimethylsiloxane polymer was prepared and spin-coated on tapered fiber. The tapered fiber with adiabatic (AD) and non-adiabatic (nAD) characteristics were fabricated by varying the up/down taper length while maintaining the waist diameter and length. Among different concentration samples only Sample 2, having metal-to-ligand ratio of 2:1, established the desired modulation depth (MD) of around 5%, which was then inserted in erbium-doped and thulium-doped fiber lasers. At first, a ring cavity erbium-doped fiber laser (EDFL) was designed, having net group velocity dispersion (GVD) in anomalous dispersion regime. The GVD was then shifted to near zero dispersion regime by increasing the erbium-doped fiber length. A conventional soliton mode-locked pulse with Kelly sidebands was observed with 8 m length of erbium-doped fiber for both SAs, prepared through composite deposition on AD and nAD tapered fiber. The mode-locked fiber laser (MLFL) in the EDFL cavity demonstrated stable characteristics observed during power development with no indication of multi-pulsing or instabilities. The oscilloscope traces and radio frequency (RF) spectrum were observed at a fundamental frequency of 9.9 MHz for both SAs. Moreover, ultrashort pulses with pulse duration of 810 fs and 845 fs were obtained with nAD and AD SA, respectively. When the length of erbium-doped fiber increased to 10 m, noise-like pulse was observed having autocorrelation trace of narrow spike riding on the broad pedestal operating at a fundamental repetition rate of 9 MHz. The pedestal pulse width of 13.9 ps and 26.7 ps were obtained with nAD and AD SA, respectively. The corresponding pulse width of spike was 164 fs and 148 fs, respectively. Likewise, the cavity with both conventional soliton and noise-like pulse demonstrated good operational stability for two hours. The AD SA performed better with high pulse energy, average output power, and RF characteristics, whereas the nAD SA possessed the smallest pulse width, higher spectral bandwidth and higher MD. A ring cavity thulium-doped fiber laser (TDFL) was constructed with 3 m length of thulium-doped fiber only. All the components used for the proposed TDFL cavity were consisted of fibers having an anomalous dispersion. Therefore, the variation in the length of thulium doped fiber would not change the operating regime of MLFL. The optical spectrum with 3-dB bandwidth of 4.47 nm centered at 1933.25 nm was obtained with nAD SA. Whereas for the AD SA, the 3-dB bandwidth and center wavelength of 4.21 nm and 1935.26 nm were observed, respectively. Moreover, ultrashort pulse, having pulse duration of 1.19 ps and 985 fs were obtained with nAD and AD SA, respectively. The power development spectra demonstrated a stable performance of MLFL, operating at fundamental frequency of 14.7 MHz without any pulse breaking or instabilities. The proposed passive MLFL in TDFL cavity demonstrated ultrashort pulse with signal-tonoise ratio greater than 50 dB and remained stable for 2 hours stability measurement. Generally, this work involves optimization of Ni-H3BTC MOF for ultrashort pulse generation; conventional soliton and noise-like mode-locked pulses. These findings suggest the viability of Ni-H3BTC-MOF as a new light-absorbing material for ultrashort pulse generations that might assist as a footing for exploring different types of available MOFs and their properties for the purpose. This work infers that MOF-based saturable absorbers can be an alternative material for generating ultrashort pulses.